Pregnancy influences on the rumen environment of Angus heifers differing in feed efficiency - Martin, M. Gabbi; Henniger, Madison T.; Clemmons, Brooke A.; Ault-Seay, Taylor B.; Cordero, Juan F.; Voy, Brynn H.; McLean, Kyle J.; Mulon, Pierre-Yves; Anderson, David E.; Myer, Phillip R. (Frontiers in Animal Science, 2024)
With an expected increase in population by 2050, the demand for high-quality protein for human consumption will increase. To improve the sustainability of US cattle production, producers and researchers have historically focused on improving the feed efficiency of steers through improvements in genetics, nutrition, and microbiome management, producing a more marketable beef product. However, without a successful pregnancy, there would be no marketable animal to feed. The objective of this study was to examine the impact of pregnancy on the rumen environment, microbial communities, and the correlation to feed efficiency status in Angus heifers. Utilizing 17 cannulated Angus heifers, feed efficiency status was determined using the GrowSafe 8000 feed intake monitoring system to monitor feed intake for a 70d trial period to calculate residual feed intake. Following the trial, heifers were bred and 40mL rumen fluid and content samples were collected every two weeks during gestation. Metagenomic DNA was extracted from the rumen samples, sequencing libraries were prepared targeting the bacterial V4 region of the 16S rRNA gene, and resultant libraries were sequenced on an Illumina MiSeq. All microbial analyses were conducted in the R environment v2.6.2 where alpha diversity, beta diversity, and differential abundances were determined. Metabolites were identified using ultra high-performance liquid chromatography high resolution mass spectrometry, and Metabolomic Analysis and Visualization Engine was used to select metabolite peaks. Differential abundance analyses using “ANCOMBC” indicated 10 amplicon sequence variants (ASVs), assigned to seven Prevotella and three Succiniclasticum, significantly varied among weeks of gestation (P<0.05). Based on a one-way ANOVA, 90 metabolites were determined significant throughout pregnancy (P<0.05). The 10 metabolites with the highest variable importance of projection scores from a partial least squares discriminant analysis were used to calculate correlations between. Of the 10 ASVs and 10 metabolites, significant correlations with feed efficiency status were found at various time points (P<0.05). The rumen microbiome and its fermentative profile were different at various time points during pregnancy with several correlations to feed efficiency status. Identifying pregnancy-related microbial and metabolite changes may aid producers to anticipate nutritional or management adjustments, ultimately contributing to the sustainability of beef production.